Kepemimpinan Perempuan dalam Politik Indonesia Perspektif Hadits An-Nasa’i Nomor 5293 - Berlian Kusmastuti, Imel; Nasrulloh (Al-Kindi, 2026)
Women’s leadership in Indonesian politics continues to develop and remains a subject of debate, particularly concerning the interpretation of the hadith narrated by an-Nasa’i No. 5293, which is often used as a basis to restrict women’s roles in leadership. This study aims to analyze women’s political leadership from an Islamic perspective by examining Surah An-Nur verse 55 and the hadith of an-Nasa’i No. 5293, and by connecting these texts with the contemporary reality of women leaders in Indonesia. This research employs a library research method, drawing upon various sources such as tafsir works, hadith collections, books, academic journals, and political regulations in Indonesia. The findings reveal that the hadith possesses a specific historical context namely the unstable political situation in Persia when the daughter of Kisra was appointed ruler. Therefore, the hadith cannot be applied universally to all circumstances and eras. In the modern context, particularly within Indonesia’s democratic system in which authority is distributed among multiple state institutions, women have legitimate opportunities to assume leadership roles. This is supported by the success of several female leaders such as Megawati Soekarnoputri, Khofifah Indar Parawansa, and Tri Rismaharini, who have demonstrated their capabilities in holding strategic public positions. Additionally, national regulations concerning women’s political representation further illustrate the state’s support for women’s participation in governance. Thus, women’s political leadership in Indonesia aligns with the Islamic principle of maslahah, which emphasizes public welfare and justice as foundations of leadership.